Analisis Konsep Restorative Justice dalam Penerapan Undang-Undang Nomor 1 tahun 2023 tentang KUHP terhadap Perbuatan yang Diancam dengan Sanksi di bawah 5 Tahun - Muhammad Ikbal (Southeast Asian Journal of Victimology, 2026)
The purpose of this study is to examine the concept of restorative justice in the implementation of Law Number 1 of 2023 concerning the Criminal Code toward acts punishable by sanctions under 5 years, as well as the factors that become obstacles in the implementation of restorative justice for criminal sanctions under 5 years. The philosophy behind the implementation of restorative justice is based on achieving a balance between perpetrators and victims, while also considering the implementation of criminal law itself, which often fails to emphasize justice and legal benefits, resulting in overcrowding in correctional institutions. The type of research used in this study is normative legal research with a descriptive qualitative approach by examining secondary data and primary legal materials which are then analyzed to obtain conclusions. The results of this study indicate that restorative justice in law enforcement is a principle in resolving cases that can serve as a recovery instrument and an alternative settlement for criminal cases through dialogue and mediation involving perpetrators, victims, the families of both parties, and other related parties in order to achieve fair and balanced agreements for both victims and perpetrators by prioritizing the restoration of conditions to their original state and rebuilding harmonious relationships within society. However, the implementation of restorative justice in Indonesia still receives negative perceptions from the public, causing uncertainty among law enforcement officials in applying the concept. Therefore, clearer and more comprehensive regulations are needed so that the implementation of restorative justice can be carried out effectively without hesitation.